Apoplastic maize fructan exohydrolase Zm-6-FEH displays substrate specificity for levan and is induced by exposure to levan-producing bacteria - Huang, Xiaojia; Luo, Wei; Wu, Silin; Long, Yuming; Li, Rui; Zheng, Fenghua; Greiner, Steffen; Rausch, Thomas; Zhao, Hongbo (International journal of biological macromolecules, 2020)
Fructan exohydrolases (FEHs) are structurally related to cell wall invertases. While the latter are ubiquitous in higher plants, the role of FEHs in non-fructan species has remained enigmatic. To explore possible roles of FEHs in maize, a full length putative Zm-6-FEH-encoding cDNA was cloned displaying high sequence similarity with cell wall invertases. For functional characterization, Zm-6-FEH protein was expressed in Picha pastoris and in Nicotiana benthamiana leaves. Enzyme activity of recombinant Zm-6-FEH protein showed a strong preference for levan as substrate. Expression profiling in maize seedlings revealed higher transcript amounts in the more mature leaf parts as compared to the growth zone at the base of the leaf, in good correlation with FEH enzyme activities. Subcellular localization analysis indicated Zm-6-FEH location in the apoplast. Noteworthy, incubation of leaf discs with levan and co-incubation with high levan-producing bacteria selectively up-regulated transcript levels of Zm-6-FEH, accompanied by an increase of 6-FEH enzyme activity. In summary, the results indicate that Zm-6-FEH, a novel fructan exohydrolase of a non-fructan species, may have a role in plant defense against levan-producing bacteria.